Le programme électoral du PSOE de 1982 : une réponse à l’opinion publique ? (Les Cahiers de Framespa)
The Spanish Socialist Workers Party‘s landslide electoral victory on the 28th of October 1982 did not just occur because the Centre-right Party, in power since 1977, was fraying and decaying. The extent of the victory is partly explained by another factor which is just as important: the public opinion had been taken into account when formulating the manifesto. This element remains crucial as we now grasp the ideological evolutions and strategies inherent in the SSWP since 1979.